Monetary inequality among households in Togo: An illustration based on the decomposition of the Gini coefficient using the Shapley value approach - Yawo Agbényégan Noglo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper aims at measuring and analysing for the first time inequality in the distribution of expenditures among households in Togo according to the characteristics of household heads. The study is based on the most recent survey (QUIBB 2006) and the monetary well-being indicator used is total real annual expenditure per adult equivalent. With regard to the decomposition of the Gini index through Shapley's approach, within-group inequality is greater than between-group inequality. These findings witness that in Togo, policy actions to reduce inequalities should first target the within-group expenditure disparities without neglecting the between-strata effects.
Keywords: D63; I31; 330; decomposition; Gini coefficient; inequality; Shapley's value; Togo